Determination of Rain Intensity Based on Rain Characteristics Observed from Rain Observation Stations Around South Jakarta - Pavita Khansa; Evi Siti Sofiyah; I Wayan Koko Suryawan (Universitas Islam Sultan Agung, 2020)
South Jakarta has the highest rainfall concentration and the most flood location in Jakarta. Therefore, an urban drainage system is needed to control surface water so flood can be prevented. This research aims to support the urban drainage system planning by determining rainfall intensity based on three methods, those are Van Breen, Bell Tanimoto, and Hasper der Weduwen. The most suitable method will be selected by comparing the value of rainfall intensity with Talbot, Sherman, and Ishiguro approach. This research reveals that the most suitable method is the Van Breen Method with the Talbot equation. The result of the calculation is rainfall intensity for 2, 5, 10, 25, 50, and 100 years rain return period, with each range 27.2 – 182.8 mm/hour, 36.8-197.6 mm/hour, 43.1-206.3 mm/hour, 51.1-216.6 mm/hour, 57-223.9 mm/hour, and 63-230,8 mm/hour.